THE CHANGES IN AEROBIC WORK CAPACITY OF THE STUDY PROGRAM "HEALTH CARE SPECIALIST" DURING THE ELEVEN YEARS PERIOD - Arnis, Voldemārs; Bole, Evita; Upeniece, Irēna; Vīnberga, Indra; Hoferte, Maruta; Gauruča, Anita; Āboliņa, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Aerobic work capacity is one of the main indicators of physical fitness and health. Aerobic work capacity depends on many factors, both physical activity level and age and gender and other factors. Aerobic work capacity falls down under the influence of sedentary lifestyle, but it can also decrease as a result of over-intensity loads. Applicants for the study program are young people who have recently graduated from the high school and people of different ages with different sporting experiences. The purpose of the research: to explore applicants aerobic work capacity of Rīga Stradiņš University study program "Health Care Specialist” and their relation to various factors and changes in the dynamics of 11 years. A total of 731 participants (268 males and 473 women) conducted the World Health Organization Bicycle ergometer test. The average level of aerobic work capacity for health care specialist applicants will increase from 2007 to 2013, but declines relatively fast between 2014 and 2017. Over the last 6 years, aerobic work capacity has fallen sharply for men as women. Body mass index does not change significantly over 11 years. The correlation between body mass index and aerobic capacity is weak. Over the last 3 years aerobic work capacity downturn trend has been particularly pronounced for women aged 20- 29.